2011
DOI: 10.1111/j.1469-0691.2010.03257.x
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms direct identification from blood culture by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) allows a fast and reliable bacterial identification from culture plates. Direct analysis of clinical samples may increase its usefulness in samples in which a fast identification of microorganisms can guide empirical treatment, such as blood cultures (BC). Three hundred and thirty BC, reported as positive by the automated BC incubation device, were processed by conventional methods for BC processing, and by a fast metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
2
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 23 publications
11
102
2
12
Order By: Relevance
“…With a special set of MALDI Sepsityper is possible to identify bacteria directly from the positive blood culture (17)(18)(19)(20)(21)(22)(23)(24)(25). Most reports describe the blood culture must be grown in automated BACTEC system vials (26,27).…”
Section: An Evaluation Of Direct Identification Of Pathogens From Blomentioning
confidence: 99%
“…With a special set of MALDI Sepsityper is possible to identify bacteria directly from the positive blood culture (17)(18)(19)(20)(21)(22)(23)(24)(25). Most reports describe the blood culture must be grown in automated BACTEC system vials (26,27).…”
Section: An Evaluation Of Direct Identification Of Pathogens From Blomentioning
confidence: 99%
“…These methods may be laborious and include several phases such as centrifugation, wash, gel separation and protein extraction. (13) obtained an accurate bacterial identification of 83.3% Gram negative bacteria and 31.8% Gram positive bacteria (28) in comparison with conventional methods. In contrast, Moussaoui et al (24) yielded better results with the accurate identification of 91.1% Gram negative and 89% Gram positive microorganisms through MALDI-TOF MS.…”
Section: Bacterial and Yeast Identification Directly From Clinical Samentioning
confidence: 99%
“…Besides, the low inoculum of microorganisms present in the samples also hampers the identification of mass spectra. Thus, several research groups have developed and assessed different protocols for the extraction of proteins from microorganisms and removal of substances that may interfere in MALDI-TOF MS analysis (2,13,20,28) . These methods may be laborious and include several phases such as centrifugation, wash, gel separation and protein extraction.…”
Section: Bacterial and Yeast Identification Directly From Clinical Samentioning
confidence: 99%
“…In one study (Ferreira et al, 2010c), no fungi (0/18) were identified at the species level and only one at the genus level. This poor performance is attributed to the relatively low load of fungi observed in positive blood culture and to the presence of residual blood protein which co-migrates during the MALDI-TOF assay, which impairs the performance of the diagnostic algorithm.…”
Section: Blood (Hemoculture)mentioning
confidence: 99%